2022
DOI: 10.1186/s12886-022-02698-z
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the vault prediction model based on the sulcus-to-sulcus diameter and lens thickness: a 925-eye prospective study

Abstract: Background To verify the accuracy and stability of the prediction formula based on the ciliary sulcus diameter and lens thickness and to analyse factors influencing the prediction results. Methods In total, 925 eyes from 506 subjects were enrolled in this prospective study between July 1, 2020, and June 30, 2021. Subjects were divided into four seasons, each spanning three months. The target vault was set to be between 300 μm and 700 μm according t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…This finding is consistent with our previous study [ 11 ] which revealed that ICA was the major risk factor for excessive vault (> 1000 μm), with every 1-degree reduction in ICA, the risk of excessive vault increased by 4%. Zhu et al [ 17 ] developed a regression equation to predict the vault when testing the accuracy of the formula they found that wide ICA, iris concavity and anteriorly positioned ciliary body may be the reasons for large prediction errors. To our knowledge, the mechanism of the relationship between the ICA and the vault has not been well elucidated, and we hypothesize that ICL haptic-related parameters may play an important role in this relationship.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is consistent with our previous study [ 11 ] which revealed that ICA was the major risk factor for excessive vault (> 1000 μm), with every 1-degree reduction in ICA, the risk of excessive vault increased by 4%. Zhu et al [ 17 ] developed a regression equation to predict the vault when testing the accuracy of the formula they found that wide ICA, iris concavity and anteriorly positioned ciliary body may be the reasons for large prediction errors. To our knowledge, the mechanism of the relationship between the ICA and the vault has not been well elucidated, and we hypothesize that ICL haptic-related parameters may play an important role in this relationship.…”
Section: Discussionmentioning
confidence: 99%
“… The Zhu formula, based on ICL size, HSTS, VSTS, and LT, was used to predict the vault. Vault (μm) = -1369.05 + 657.121 × ICL size (mm)—287.408 × HSTS (mm)—432.497 × LT (mm)—137.33 × VSTS (mm) [ 11 ]. The predicted vault was obtained by inputting the actual implanted ICL size, HSTS, VSTS, and LT into Excel.…”
Section: Methodsmentioning
confidence: 99%